Hubungan Indeks Massa Tubuh, Persen Lemak Tubuh, Asupan Zat Gizi dengan Kekuatan Otot - Setiowati, Anies (Universitas Negeri Semarang, 2014)
This study aimed to determine the relationship of body mass index, percent body fat and nutrient intake degan muscle strength. The method used cross-sectional study. Sample were students in high school basketball athletes Light Nations Semarang 15-18 years old .. weighing as much as 11 weight carried by digital scales, percent body fat measured by bioelectrical impedance analyzer (BIA) brand Corona, muscle strength with dynamometer. Data were analyzed using test and Spearman Person Product Momment. Statistical test results with the results obtained by the average normal BMI (21.6 ± 3.57), percent body fat (15.81 ± 3.63%), the level of energy consumption (54.45 ± 6.77%) and protein (63.93 ± 11.43%) less, the percentage of carbohydrate intake (68.97 ± 6.3%) and the percentage of normal fat intake (29.95 ± 4.88%). There is a relationship percent body fat with muscle strength (r = -0.670, p = 0.024) and protein intake relationship with muscle strength (r = 0.624, p = 0.04).